Implementasi Pembelajaran Teknologi Informasi Berbasis Augmented Reality di Sekolah Menengah Kejuruan - Muhammad Rinov Cuhanazriansyah; Yuniana Cahyaningrum; Dea Ayu Nurul Qolby (JRTI (Jurnal Riset Tindakan Indonesia), 2023)
Augmented Reality (AR) is a technology that combines virtual objects with real objects. One of the fields that uses AR technology is the field of education, especially for learning information technology, computer installation materials. used as a learning aid to make students better understand the material provided. This study describes the use of AR technology in learning about the human excretory system using AR technology while aiming to increase students' digital literacy and optimize the use of digital media in the learning process. In making learning applications using the AR method, the authors use the Marker Based Tracking AR method. The purpose of this research is to make it easy for students to learn and understand the material, so that learning becomes more interesting and not boring. In this application each object is displayed with a visual image in 3D using animation, sound and attractive colors. The research methods in this study are literature studies, field studies, and sample calculations. The results of this study are mobile applications that are used as a supporting tool to assist the learning process.